The Potential of Forest Betel Weed as Raw Materials for Botanical Pesticides in West Sumatra - Eka Candra Lina; Novri Nelly; Rusli Rustam; Prima Fithri; Rayhan Fadhlurrahman; Joko Prasetyo (Warta Pengabdian Andalas)
Forest betel (Piper aduncum) includes weed plants from the Piperaceae family that can be used as the main ingredient in the manufacture of environmentally friendly pest control technology, also known as botanical pesticides. Botanical pesticides from P. aduncum have the active compound dillapiol, which can control pests in various plants, especially horticulture. Commercialization of botanical pesticides needs to be done because the product meets the standards for pest control and is available in sufficient quantities on the market. The partnership was initiated by involving local communities as providers of raw materials. Surian area, Solok Regency, West Sumatra, Indonesia, has an area where P. aduncum plants dominate, so it has the potential to provide raw materials. Socialization activities about the potential of forest betel fruit or P. aduncum were given to prospective partner communities. Furthermore, training activities on handling P. aduncum fruit were also provided so that partners had sufficient knowledge and skills to proceed. At the same time, an analysis of P. aduncum fruit extract from the Surian area was also carried out. Sampling was carried out in the Surian area, and then the material was sorted, dried, refined, sieved, maserase, and extracted. Identification of dillapiol content was carried out using GC-MS. The analysis results showed that P. aduncum fruit extract was known to have an average yield of 0.1% with a dillapiol content of 12.23% at a retention time of 19.925 minutes.